Pater’s Scholar and the Hypertext - Martine Lambert-Charbonnier (Cahiers Victoriens et Edouardiens)
The hypertext is becoming a new medium for scholarship, allowing quick and universal sharing of knowledge as well as providing for scholarly criticism a new text model. Walter Pater raised the issue of scholarship in his time and his view may help us assess how the hypertext could best be used in Paterian studies. The hypertext may be appropriate for highlighting intertextuality and presenting Pater’s extensive culture. However, is the author’s intention not undermined when texts are opened to other texts while Pater saw his works as fully composed structures? The problem is even more complex when it comes to hypermedia. The hypertext suggests a new area of research around time/space scale shifts in Pater’s works, for which Jacques Fontanille’s comparative semiotics provide a methodology. After raising the issue of scholarship, the hypertext then leads us to consider Pater’s style in a new light and to explore relations between literature and the spatial arts in his works.